Input price effect on productivity gains in the United States railroad industry - Azrina Abdullah Al-Hadi,; Peoples, James (Penerbit Universiti Kebangsaan Malaysia, 2016)
This study examines factor input price effects on productivity in the railroad industry. Past research examining productivity trends in this industry limit their analysis to the effect of non-factor input prices. This study contributes to the literature by considering the effect of input prices on railroad productivity. Such an analysis significant in part because of the importance of fuel prices and wages as drivers of cost in this industry. Findings suggest that price effects are not the main source of changes in productivity. However, among the price effects, the price of material and price of way and structures show larger and significant magnitudes in explaining the sources of changes in productivity compared to other prices. Interestingly, price of labor and price of fuel are the input prices that contribute the least to changes in unit cost.